Climate-friendly technologies in the mobile air-conditioning sector: A patent citation analysis - Tilmann Rave; Frank Goetzke (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2011)
The development of climate-friendly technologies and its diffusion across countries is of key importance to slow climate change. This paper considers technologies in the mobile air-conditioning (MAC) sector which is a major contributor of fluorinatedgreenhouse gas emissions. Using patents as an indicator of innovations and patent citations as a proxy for knowledge flows the inducement of new environmental and non-environmental technologies and its diffusion within and across countries and withinand across patent applicant- and firm-types is analyzed. We find that most environmental patents originate from Germany and the US and are filed by individuals rather than firms. Most knowledge flows take place within countries. Regarding cross-countryflows most environmental knowledge diffuses from French and German patents, which is likely to be a result of regulatory activities in Europe and intensified research on environmentally benign MAC systems. Yet, this exchange of knowledge is not very intensive and stable, so that the impact of EU regulations on US and Japanese patenting behaviour remains fairly weak.
Keywords: Q55; O33; O38; C21; 330; Environmental innovation; patent; count data models; Klimaanlage; Kraftfahrzeug; Umwelttechnik; Innovation; Patent; Klimaschutz; Bibliometrie; Welt